PERBEDAAN PERSEPSI PENILAIAN PELANGGAN ANTARA KONSUMEN LOYAL DENGAN KONSUMEN PENDATANG BARU PADA PT. ASTRA INTERNATIONAL - Septiawan, Putu Eka; Suryani, Alit (E-Jurnal Manajemen, 2017)
This study aims to determine the differences between consumer perception and consumer loyal newcomers in relation to services, the purchase of products and facilities at PT. Astra International Tbk-Honda Denpasar. Its population is loyal customers and consumers newcomers. The number of samples in this study were 100 respondents defined by purposive sampling technique. The data collection is done by distributing questionnaires. The data analysis technique used is test independent t-test. The analysis showed a significant difference between loyal customers with new entrants consumers in relation to services, the purchase of products and facilities. PT. Astra International Tbk-Honda Denpasar expected to improve the service delivered to consumers and consumer loyal newcomers. So as to provide comfort for loyal customers and consumers newcomer at the time dating to visit.
Keywords: services; product purchase; facility